MODEL PEMBELAJARAN GENERATIF UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK - Afnita Sandini (Jurnal Edukasi dan Penelitian Matematika, 2020)
Mathematical concept understanding of Indonesian students is classified as low. It is indicated by various studies about mathematics learning outcome of Indonesian student. This issue is caused by the low participating student in learning process. This study aims to describe the influence of generative learning model on mathematical concept’s understanding of student. The data collected as relevant article was reviewed and analyzed to get the results. The results indicated that mathematical concept understanding of student increase and student more participate on learning process by using generative learning model. Keywords__ Mathematical concept understanding, Generative learning model, Student